THE ROLE OF MEDIATION IN RESOLVING NATIONAL AND INTERNATIONAL DISPUTES: PAST, PRESENT AND FUTURE. - Singh, Deo Narayan; Mani Pratap; Roy, Rana Navneet (ShodhKosh: Journal of Visual and Performing Arts, 2023)
International conflicts are a natural part of the world, resulting from a variety of political, economic, and social issues. Such disputes emerge in the international regime for a variety of reasons. Conventional conflict resolution techniques, including litigation and arbitration, can involve drawn-out processes and combative exchanges, which might make tensions between parties worse. On the other hand, mediation provides a cooperative and adaptable method that promotes fruitful discussion and win-win solutions. This article explores the function of mediation as a method of settling international disputes, looking at how it is used in various legal systems and the difficulties it encounters in India.